PENYEBARAN INJIL DAN TINGGALANNYA DI KAMPUNG NAU DAN WAREN KABUPATEN WAROPEN - Usmany, Desy Polla (Jurnal Penelitian Arkeologi Papua dan Papua Barat, 2013)
The presence of Christians in Wandamen Bay, whose life is orderly and peaceful, causing old people in Waropen asked the Dutch to also spread the gospel in their village. Some teachers of the gospel is then sent to Waropen. The purpose of this paper is to determine the religious system Waropen before the entry of Christianity, chronology and impact evangelism and missionary history remains in Waropen, especially in Nau village and Waren village. The research method used is the historical method. Evidence remains, the early history of the spread of the gospel remains can still be found on the island of Nau and Waren, Waropen.AbstrakAdanya orang-orang Kristen di Wandamen Papua, yang hidupnya teratur dan penuh kedamaian, menyebabkan orang-orang tua di Waropen meminta kepada Belanda agar Injil juga disebarkan di kampung mereka. Beberapa guru injil kemudian dikirim ke Waropen. Tujuan penulisan ini adalah untuk mengetahui sistim religi orang Waropen sebelum masuknya agama Kristen, kronologi pekabaran Injil serta dampak dan tinggalan sejarah pekabaran injil di Waropen, khususnya di Kampung Nau dan Kampung Waren. Metode penelitian yang gunakan adalah metode sejarah. Bukti tinggalan-tinggalan sejarah awal penyebaran injil masih dapat ditemukan di Pulau Nau dan Waren, Waropen.